2006
DOI: 10.1088/1748-3182/1/4/s06
|View full text |Cite
|
Sign up to set email alerts
|

Passive cambering and flexible propulsors: cetacean flukes

Abstract: The flukes are the primary locomotor structure in cetaceans, which produce hydrodynamic thrust as the caudal vertebrae are oscillated dorso-ventrally. Effective thrust generation is a function of the kinematics of the flukes, the angle of attack between the flukes and the incident water flow, and the shape of the flukes. We investigated the effect of bending within the caudal region of odontocete cetaceans to determine how changes in angular displacement between caudal vertebrae could effect passive shape chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…While previous work has shown that movements of the tailstock passively affect the shape of the flukes (Fish et al, 2006), there is no evidence documenting that movements (or removal) of the fluke influence the shape of the tailstock. The animal was placed on its left side and positioned longitudinally such that its rostrum and the caudal vertebrae of the tailstock were on the center line of the apparatus.…”
Section: Mechanical Testsmentioning
confidence: 88%
“…While previous work has shown that movements of the tailstock passively affect the shape of the flukes (Fish et al, 2006), there is no evidence documenting that movements (or removal) of the fluke influence the shape of the tailstock. The animal was placed on its left side and positioned longitudinally such that its rostrum and the caudal vertebrae of the tailstock were on the center line of the apparatus.…”
Section: Mechanical Testsmentioning
confidence: 88%
“…During swimming, the cambering of flukes of a cetacean can increase the production of hydrodynamic forces, particularly during direction reversal in the oscillatory cycle [18]. Ahlborn et al studied the effect of tail stiffness in the fast-start swimming of fish [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of flexibility has been studied mainly in flapping foils with 2-D (heaving and pitching) kinematics (Liu and Bose, 1997;Prempraneerach et al, 2003). It has been demonstrated numerically Zhu and Shoele, 2008) and experimentally (McHenry, 1995;Triantafyllou et al, 2005;Fish et al, 2006;Lauder et al, 2006; that flexibility is instrumental to the production of propulsive forces and to the efficiency of flapping locomotion. When properly set along the chord and the span, passive flexibility improves propulsive efficiency, and under the correct operating conditions can increase peak thrust and lift forces.…”
Section: Introductionmentioning
confidence: 99%